2018
DOI: 10.1021/acschemneuro.7b00509
|View full text |Cite
|
Sign up to set email alerts
|

Pharming for Genes in Neurotransmission: Combining Chemical and Genetic Approaches in Caenorhabditis elegans

Abstract: Synaptic transmission is central to nervous system function. Chemical and genetic screens are valuable approaches to probe synaptic mechanisms in living animals. The nematode Caenorhabditis elegans is a prime system to apply these methods to discover genes and dissect the cellular pathways underlying neurotransmission. Here, we review key approaches to understand neurotransmission and the action of psychiatric drugs in C. elegans. We start with early studies on cholinergic excitatory signaling at the neuromusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 122 publications
(228 reference statements)
0
9
0
Order By: Relevance
“…We then tested if the cilia-mediated neuronal necrosis evoked by P. ostreatus hyphae is a feature distinct from the effect elicited by anthelmintic drugs that can also paralyze nematodes, such as A B C D ivermectin, aldicarb, and levamisole, which also paralyze C. elegans. Research over the past 4 decades has revealed that these anthelmintic drugs act at neuromuscular junctions (32,33), targeting nicotinic acetylcholine receptors (levamisole) (34), glutamategated chloride channels (ivermectin) (35), and acetylcholinesterase (aldicarb) (36). We examined if any of these drugs cause necrosis of the ciliated sensory neurons, but there were no indications of neuronal necrosis in C. elegans that were paralyzed by aldicarb, levamisole, or ivermectin (Fig.…”
Section: Cilia-dependent Paralysis By P Ostreatus Is Evolutionarily mentioning
confidence: 99%
“…We then tested if the cilia-mediated neuronal necrosis evoked by P. ostreatus hyphae is a feature distinct from the effect elicited by anthelmintic drugs that can also paralyze nematodes, such as A B C D ivermectin, aldicarb, and levamisole, which also paralyze C. elegans. Research over the past 4 decades has revealed that these anthelmintic drugs act at neuromuscular junctions (32,33), targeting nicotinic acetylcholine receptors (levamisole) (34), glutamategated chloride channels (ivermectin) (35), and acetylcholinesterase (aldicarb) (36). We examined if any of these drugs cause necrosis of the ciliated sensory neurons, but there were no indications of neuronal necrosis in C. elegans that were paralyzed by aldicarb, levamisole, or ivermectin (Fig.…”
Section: Cilia-dependent Paralysis By P Ostreatus Is Evolutionarily mentioning
confidence: 99%
“…More generally, mammalian researchers have long conducted high-throughput screening of drugs using simple, unambiguous behaviours, such as the time rodents struggle to escape during tail suspension or forced swimming (Castagné et al, 2011). Similar approaches are used in invertebrate model species (Nichols et al, 2012;Blazie and Jin, 2018) and could be more widely developed in non-model organisms. Efficient assays may uncover novel invertebrate-specific ligands that can be assessed in detail at the molecular level, and selected for investigations of complex behaviours such as aggression, anxiety and mate choice.…”
Section: Linking Heterologously Expressed Receptors To Endogenous Recmentioning
confidence: 99%
“…Importantly, the C. elegans egg-laying system uses molecular mechanisms of serotonin signaling that have counterparts in the vertebrate brain. HSNs use conserved pathways for the synthesis, storage, and release of serotonin (14)(15)(16)(17)(18). G protein-coupled serotonin receptors that are homologous to mammalian HTR2 and HTR7 mediate activation of ELMs (19,20), and these nematode serotonin receptors signal via conserved G q and G s subunits to activate highly conserved secondmessenger signaling cascades.…”
mentioning
confidence: 99%